Trust and the Performative Construction of Markets - Jens Beckert (Max Planck Institute for the Study of Societies, 2005)
The concept of trust has recently been rediscovered, especially in the fields of economic sociology and organization theory. Nevertheless, the actual functioning of trust in markets has only been understood incompletely up to now. As this paper argues, one reason for this is that conceptualizations of trust have focused primarily on the decision-making process of the trust-giver. The contribution of the trust-taker, however, has not been comprehensively investigated. I propose understanding trust as a tranquilizer in market relations that is partly produced in the situation itself by the performative acts of self-presentation of the trust-taker. On the basis of a taxonomy of four strategies, the final part of the paper demonstrates the consequences that result for the understanding of the functioning of markets from this conceptualization of trust relations. – – Das Konzept des Vertrauens wurde insbesondere in der Wirtschafts- und Organisationssoziologie während der letzten Jahre wiederentdeckt. Dennoch ist die Funktionsweise von Vertrauen auf Märkten bisher nur unvollständig verstanden. Der Grund hierfür ist, so die in dem Papier entwickelte These, dass die Konzeptualisierungen von Vertrauen hauptsächlich die Entscheidungsprozesse des Vertrauensgebers untersuchen, den Beitrag des Vertrauensnehmers für das Zustandekommen von Vertrauensbeziehungen jedoch nur unvollständig beleuchten. Es wird vorgeschlagen, Vertrauen als ein Beruhigungsmittel in Tauschbeziehungen zu verstehen, das entscheidend durch die performativen Akte der Selbstdarstellung des Vertrauensnehmers in der Handlungssituation erzeugt wird. Im letzten Abschnitt wird auf der Basis einer Heuristik von vier Strategien gezeigt, welche Perspektive sich aus dieser Vertrauenskonzeption für das soziologische Verständnis der Funktionsweise von Märkten ergibt.
Keywords: 300